Chronic Active Antibody-Mediated Rejection Is Associated With the Upregulation of Interstitial But Not Glomerular Transcripts - Trailin, Andriy; Mrazova, Petra; Hruba, Petra; Voska, Ludek; Sticova, Eva; Slavcev, Antonij; Novotny, Marek; Kocik, Matej; Viklicky, Ondrej (Frontiers in Immunology, 2021)
Molecular assessment of renal allograft has already been suggested in antibody mediated rejection (ABMR), but little is known about gene transcripts patterns in particular renal compartments. We used laser capture microdissection coupled with quantitative RT-PCR to distinguish transcripts patterns in glomeruli and tubulointerstitium of kidney allografts in sensitized retransplant recipients at high ABMR risk. The expression of 13 genes was quantified in biopsies with acute active ABMR, chronic active ABMR, acute tubular necrosis (ATN) and normal findings. The transcripts were either compartment specific (TGFB1 in glomeruli, HAVCR1 and IGHG1 in tubulointerstitium), ABMR specific (GNLY), or follow-up specific (CXCL10, CX3CR1). The transcriptional profile of early acute ABMR shared similarities with ATN. CXCL10 and TGFB1 transcripts were increased in glomeruli in both acute and chronic active ABMR. Chronic active ABMR was associated with the upregulation of most genes (SH2D1B, CX3CR1, IGHG1, MS4A1, C5, CD46 and TGFB1) in the tubulointerstitium. In this study we showed distinct gene expression patterns in specific renal compartments reflecting cellular infiltration observed by conventional histology. In comparison with active ABMR, the chronic active ABMR is associated with the increased transcripts of tubulointerstitial origin.